Measurements of adsorption kinetics at sub atmospheric pressures employing volumetric apparatus - Mohammad Hafiz Ahmad Kamal. (2013)
With increasing demand in cooling-based appliances such as air conditioners in today’s society, more non-renewable energy sources which release greenhouse gases are being used. As a result, there is an increase in demand for greener technologies that are also just as efficient. One solution is the usage of adsoption technology which uses renewable and harmless materials, and natural refrigerant such as ethanol vapour and water vapour. This leads to the technology being increasingly seen as a suitable alternative for future chillers. Therefore, thorough research on this technology is currently being conducted all over the world.